The Impact of Personality: Extrovert vs. Introvert on the Ability in Syntax in Essay Writing - Zainuddin Zainuddin (Universitas Syiah Kuala, 2016)
The main purpose of this study was to find out if there would be any significant difference in scores for syntax in essay writing between extrovert and introvert EFL learners. The quantitative data were collected by applying writing rubrics from Brown (2007). The participants of this study were 40 English learners (20 extroverts and 20 introverts) at Universitas Negeri Medan, Indonesia. The data were analyzed by using Statistical Package for the Social Sciences (SPSS) version 2.0. The findings of this study indicated that there was a significant difference in the scores for syntax between extrovert and introvert learners. In this study, introvert EFL learners did better than extrovert EFL learners in constructing sentences (syntax). Thus, both groups still have an equal chance to improve their ability in a learning foreign language particularly in writing skills but extrovert EFL learners must pay more attention to using good syntax because they tend to be careless and less correct in constructing their phrases when doing a writing task.